Aerodynamic analysis of a light aircraft at different design stages - Kostić Ivan A.; Stefanović Zoran A.; Kostić Olivera P. (FME Transactions, 2014)
During the evolution of an airplane aerodynamic design, proper calculation methods and software tools should be utilized, which correspond to the airplane category and project development level. In case of light aircraft, the general trend is the application of analytical and semiempirical methods at the initial stages, combined with simplified - inviscid CFD computational models, and fairly complex viscous CFD analyses at higher design levels. At the present stage of light aviation development, it is assumed that the contemporary design tools for each of those steps should be appropriate enough, so that they actually verify and additionally fine-tune each other's results. This paper describes the calculation tools and methods applied during the aerodynamic analyses of a new light aircraft at different development stages, and compares the results obtained by them, with the aim to verify and support the above statement, considering light aircraft aerodynamic design.